Determinasi RAROC Bank menggunakan Faktor Internal dan Faktor Eksternal Bank serta Size sebagai Variabel Moderasi - Tarigan, Paul Augustin; Manurung, Adler Haymans (Universitas Batanghari Jambi, 2024)
This study aims to explore the influence of internal and external company factors on bank profitability with size as a moderating variable. The company's financial ratios and macroeconomic variables are used to determine bank profitability, specifically the Risk-Adjusted Return on Capital (RAROC). A panel data model is employed to determine the RAROC in Indonesia for the period 2014 to 2023. This study finds that Non-Performing Loans, Electricity Consumption, Oil Prices, Exchange Rate, and FED Rate do not affect RAROC. However, Net Interest Margin and Total Assets have a significantly negative effect on RAROC, while Market Power has a significantly positive effect on RAROC. Additionally, Total Assets strengthen the negative effect of Non-Performing Loans and Net Interest Margin on RAROC, while Total Assets strengthen the positive effect of Market Power, Electricity Consumption, Oil Prices, Exchange Rate, and FED Rate on RAROC.